Multimode Memories with Longitudinally Broadened Ensembles - Nunn, J; Surmacz, K; Waldermann, R; Lee, K; Reim, K; Lorenz, V; Wang, Z; Jaksch, D; Walmsley, I; IEEE (2008)
Quantum storage of multiple optical modes affords improved performance for quantum repeaters. We present new analytic and numerical results unifying the scaling of the multimode storage capacity for various memory protocols in artificially broadened ensembles. © 2008 Optical Society of America.